2002
DOI: 10.1093/molehr/8.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Th1- and Th2-like cytokine production by first trimester decidual large granular lymphocytes is influenced by HLA-G and HLA-E

Abstract: During normal early pregnancy, a particular immune environment in the decidua and the expression of non-classical HLA-G and HLA-E molecules on the invading trophoblast are assumed to be essential for the tolerance of the fetus. To assess whether HLA-G and HLA-E influence the cytokine production of their putative target cells [large granular lymphocytes (LGL)], we analysed the concentrations of tumour necrosis factor (TNF-alpha), interferon (IFN)-gamma, interleukin (IL)-10, IL-13 and granulocyte-macrophage colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 21 publications
2
40
0
4
Order By: Relevance
“…Thus, some disease states may mimic the physiological inflammation associated with pregnancy. Numerous cytokines and chemokines, including GM-CSF, IFN-g, and TNF-a, are produced by the decidua (53,54). In tumors, these cytokines and growth factors are known to upregulate neutrophil expression of CD191 and CD195, and to prime neutrophil migration toward CC chemokines, such as CCL2-5 (55-57).…”
Section: Il2rgmentioning
confidence: 99%
“…Thus, some disease states may mimic the physiological inflammation associated with pregnancy. Numerous cytokines and chemokines, including GM-CSF, IFN-g, and TNF-a, are produced by the decidua (53,54). In tumors, these cytokines and growth factors are known to upregulate neutrophil expression of CD191 and CD195, and to prime neutrophil migration toward CC chemokines, such as CCL2-5 (55-57).…”
Section: Il2rgmentioning
confidence: 99%
“…Decidual T cells can produce cytokines including interleukin (IL)-3, IL-4, transforming growth factor (TGF)-b 1 , TNF-a and interferon (IFN)-g [42][43][44][45] and it has been suggested that deficient production by decidual T cells of cytokines, such as IL-4 and LIF, may lead to pregnancy failure [47]. Recently, the non-classical class I HLA-G and HLA-E molecules, both of which are expressed by fetal trophoblast cells, have been reported to suppress production by isolated first-trimester uterine NK cells of cytokines including IL-10, IL-13, TNF-a, granulocyte macrophage colony-stimulating factor (GM-CSF) and IFN-g [49]. Whether HLA-G and HLA-E regulate the production of cytokines by decidual T cells and macrophages is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…proposed to be involved in the modulation of maternal immune responses and has for instance been shown to inhibit cytokine production and reduce NK cell cytotoxicity, to eliminate activated cytotoxic CD8 + T cells and to induce production of TGF-β by APCs (Rieger et al, 2002;Hunt et al, 2005). Although less pronounced, HLA-E has also been shown to inhibit NK cell cytotoxicity (King et al, 2000a).…”
Section: Immune Regulation During Pregnancymentioning
confidence: 99%